An Attempt to Attain New Information in Reconstruction of Road Traffic Accidents Applying Digital Image Processing - Paliska, Dejan; Batista, Milan; Starin, Roman; Fabjan, Daša (Promet - Traffic&Transportation, 2012)
Court expertise dealing with the reconstruction of road traffic accidents often have to take into account the possibility that an accident could have been a set-up. Such suspicions can be eliminated only by considering all the evidence material from the accident scene. In case of photographic material experts come across the missing material, bad lighting, lack of contrast, different angle perspectives, blurring, omitting important details, etc. Therefore, different methods in forensics image processing have been developed. Most of these methods are primarily used in the processing of different types of photographic material, but some can be applied in the field of road accidents analyses. This paper shows the implementation of digital image processing methods used for processing of remotely sensed imagery. Even though the photographic evidence is incomplete, it is possible to determine the position and dispersion of different materials. This gives the experts additional information that can help in understanding with relatively high probability if the collision between vehicles occured at all and if it did, where. The paper consists of the presentation and description of methods used for digital image processing in a real case study while reconstructing the road accident. KEY WORDS: road traffic accidents, forensics, induced traffic accidents, image classification, digital image processing